Identifying critical research gaps that limit control options for invertebrate pests in Australian grain production systems. Issue 1 (8th February 2019) - Macfadyen, Sarina; Moradi‐Vajargah, Mona; Umina, Paul; Hoffmann, Ary; Nash, Michael; Holloway, Jo; Severtson, Dusty; Hill, Matthew; Van Helden, Maarten; Barton, Madeleine
Abstract: Integrated Pest Management (IPM) is often described as a knowledge‐intensive approach to invertebrate pest management, requiring information on the biology, ecology and phenology of a pest combined with an understanding of the interactions between crop growth and pests and between pests and their natural enemies. We conducted a systematic quantitative literature review to summarise what is known about pest and natural enemy species common to Australian grain production systems, based on 1513 published and unpublished research studies. Drawing on this information, we address three issues: what are the knowledge gaps in relation to grain pests and their natural enemies, do these knowledge gaps limit the development of an IPM package for grain growers in Australia and what further ecological or biological information might growers require to enhance the use of IPM approaches for managing pests? The main gaps identified include a lack of understanding around specific factors that lead to pest outbreaks or factors that could be useful for predicting when and where pest outbreaks will occur in the future. Monitoring techniques for many pests are not well developed, and therefore, it is difficult to link the density recorded in a field with crop damage and yield loss and to develop economic thresholds that can be linked with intervention decisions. For most natural enemies, the impact in terms of reduction in pest numbers has not been quantified, with very few studies including both pests and natural enemies together. There is large variability in the level of control provided by natural enemies between years and regions, and the factors leading to this variability are not well understood. Finally, the lack of taxonomic resolution for individual species within groups is identified as a critical knowledge gap. We suggest that a more comprehensive fundamental knowledge base is required across the invertebrate community in grain systems aimed at reducing insect pest outbreaks, combined with a greater depth of understanding in monitoring strategies for pests that contribute to pesticide‐use decisions.